Trends and advances in sustainable bioethanol production by marine microalgae: A critical review. (15th April 2022) - Maity, Sudatta; Mallick, Nirupama
Abstract: Owing to the current issues of rapid urbanization and motorization, worldwide petroleum oil demand is increasing obstinately, which is another way of affecting the economy of a nation. The depleting fossil fuel reserves and increasing emission of greenhouse gases have raised the concern for the pursuit of alternative sustainable fuels. Bioethanol can potentially accomplish the need for a substitute for petroleum fuel. However, ascertaining environment-friendly and renewable feedstock for bioethanol is one of the major constraints towards commercialization. Due to the unsustainable approaches of the first two generation feedstocks, the incorporation of marine microalgae, both prokaryotic and eukaryotic, as third-generation feedstock for bioethanol production has been broadly considered by the researchers. Vast resources, the capability to grow in non-potable seawater, and the presence of unique metabolites ascertain marine microalgae for the major drive over its freshwater counterparts in the bioethanol industry. Despite being a promising one, research on marine-based bioethanol production is still in its infancy. This review thus highlights the prospects of marine microalgae for bioethanol production along with different hydrolysis and fermentation techniques for biomass conversion. An insight into the economically sustainable cultivation and harvesting methods, strategy for carbohydrate augmentation for a revolutionary advancement in bioethanol production have also been discussed. This assessment is also crucial in providing ideas for potentially implementing marine microalgal resources to commercialize bioethanol production. Graphical abstract: Image 1 Highlights: Marine microalgae and cyanobacteria were prioritised for bioethanol production based on economic viability. Operational marine microalgal cultivation methods considering seawater nutrient and technical feasibility were compared. Various cultural parameters involving carbohydrate augmentation in microalgae were discussed. Recent advancements of marine-derived microorganisms and their enzymes in fermentation process were mentioned. Commercialization constraints and their plausible strategies were hypothesized in this article.